Comparative Analysis of Water Quality Using Pollution Index Method and BCWQI in Cisanggarung River - Naufal Firdaus Bimantara; Ferdinan Novrizal; Syahrul Ramdhani; Heri Pramawan (Jurnal Indonesia Sosial Teknologi, 2025)
Assessment of water quality status is crucial to carry out as part of the efforts to maintain water quality, ensuring its use in community life meets the established standards. This is in stark contrast to the numerous community activities that often pollute the water content in rivers, leading to a decline in water quality and adverse effects on the people who use that water. This research is crucial for determining the quality status of water in the Cisanggarung River, as well as for comparing the water quality status in the upstream section of the Cisanggarung River using the Pollution Index and the British Columbia Water Quality Index (BCWQI). The average Pollution Index value in the Cisanggarung River is 1.192, categorized as Slightly Polluted. At the same time, the water quality status in the Cisanggarung River has an average score of 26.24, indicating a level of Fair (slightly polluted). Based on the results of determining water quality status using two methods, it can be concluded that the British Columbia Water Quality Index is the most suitable method for use in the Cisanggarung River (BCWQI).